Emission permission. - Ingebretsen, M. (IEEE spectrum)
A decade from now, one of the world's most vibrant and unusual markets will be dealing in our most notorious overabundant commodity-namely, the greenhouse gases (GHGs) believed to cause global warming. The stock in trade will be permits allowing companies to emit specific quantities of carbon dioxide, methane, and other kinds of GHGs. No such world market has been officially sanctioned as yet, but some countries already have launched national markets, with private companies established as brokers, and trading has taken place on a trial basis. If, as expected, the Kyoto Protocol takes force internationally, it will be a powerful inducement for businesses in countries that have approved the protocol to join in the trade. The main point of emissions trading is to reduce the overall cost of meeting emissions targets by giving industry strong incentives to meet goals and the flexibility to find the most cost-effective solutions. Organizations that manage to emit less than their allotted quota of gases-by retrofitting plants, building cleaner or more efficient plants, or just shutting some down-can profit by selling unneeded emission permits to companies unable to stay within their quotas.